2020
DOI: 10.1097/yco.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

The development of the social brain in baby siblings of children with autism

Abstract: Purpose of review Impairments in social interaction/communication become apparent after 12 months of age in children who develop Autism spectrum disorder (ASD). Studies of baby siblings of children with ASD provide the means to detect changes in the brain that are present before behavioral symptoms appear. In this review, advances from brain imaging studies of infant siblings over the past 18 months are highlighted. Recent findings During the first 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Some pathogenic factors have not been clearly identified ( 4 , 5 ). For example, studies have found that some brain regions of children with autism have abnormal anatomical structures or abnormal brain function activities ( 6 , 7 ), but whether cerebral blood perfusion in abnormal brain regions is also abnormal is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some pathogenic factors have not been clearly identified ( 4 , 5 ). For example, studies have found that some brain regions of children with autism have abnormal anatomical structures or abnormal brain function activities ( 6 , 7 ), but whether cerebral blood perfusion in abnormal brain regions is also abnormal is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a group of neurodevelopmental disorder with the onset in early childhood, characterized by impairment in communication, and social interaction, rigidity of interests, and repetitive stereotypical behaviors ( 1 4 ). The incidence of ASD is increasing worldwide, while the etiology and pathogenesis of autism are poorly understood and no drug is available ( 5 , 6 ). Children with autism are mainly treated with rehabilitation intervention, and there is no specific treatment yet.…”
Section: Introductionmentioning
confidence: 99%
“…Children with autism are mainly treated with rehabilitation intervention, and there is no specific treatment yet. Studies have shown that early and reasonable systematic rehabilitation intervention can improve the symptoms of most children, and even obtain a basic “recovery.” The earlier the rehabilitation intervention, the better the recovery of children, which requires clinicians to accurately diagnose children with autism at an early stage ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the early diagnosis of ASD is mainly based on the clinical symptoms, but most children with ASD have no typical clinical manifestations, which makes early diagnosis very difficult. However, some researches have reported appropriate systematic rehabilitation interventions in the early stages of autism could improve the symptoms of most patients ( 7 , 8 ). It is widely accepted in the medical community that the earlier rehabilitation interventions are provided to children with ASD, the better prognosis will be.…”
Section: Introductionmentioning
confidence: 99%